World Health Organization building blocks in rural community health services: An integrative review - Stockton, Deborah A. (Health Sci Rep, 2021)
INTRODUCTION: Developing and adapting health service models to effectively meet the needs of rural and remote communities is an international priority given inequities in health outcomes compared with metropolitan counterparts. This integrative review aims to inform rural and remote health service delivery systems by drawing on the WHO Framework building blocks to identify lessons learned from the literature describing experiences of rural and remote community health service planning and implementation; and inform recommendations to strengthen often disadvantaged rural and remote health systems for policy makers, health service managers, and those implementing international healthcare initiatives within these contexts. METHODS: The integrative review examined the literature reporting rural and remote community health service delivery published from 2007 to 2017 (the decade following the release of the WHO Framework). Using an analytic frame, a structured template was developed to extract data and categorized against the WHO building blocks, followed by a synthesis of the key findings. RESULTS: This integrative review identified that WHO Framework building blocks such as “Service Delivery” and “Health Workforce” are commonly reflected in rural and remote community health service delivery literature in the decade since the Framework's release. However, others such as “Sustainable Funding and Social Protection” are less commonly reported in the literature despite these elements being identified by the WHO as being integral to successful, sustainable health service delivery systems. CONCLUSIONS: We found that collaboration across the health system governance continuum from local to policy level is an essential enabler for rural and remote health service delivery. Community‐based participatory action research provides an opportunity to learn from one another, build capacity, optimize service model suitability, and promotes cultural safety by demonstrating respect and inclusivity in decision‐making. Policy makers and funders need to acknowledge the time and resources required to build trust and community coalitions to inform effective planning and implementation.